2022
DOI: 10.1037/cns0000316
|View full text |Cite
|
Sign up to set email alerts
|

Accurately measuring nonconscious processing using a generative Bayesian framework.

Abstract: Despite considerable interest in subliminal effects, fundamental questions about the proper way of examining them remain unanswered, sowing doubts regarding the veracity of published results. A central question is whether observed effects result from nonconscious processing rather than from some stimuli being consciously perceived by participants which are missed due to error in the awareness measurement. Here, we suggest a solution that implements a Bayesian modeling approach to measure the behavioral effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Statistical tools can address this and other issues that arise from the use of awareness measures that are less than perfectly reliable. Employing tools like the one we briefly described at the end of Section 2 as well as more advanced ones (e.g., Goldstein et al, 2021) would allow the field to advance with greater confidence in the veracity of results. This, we hope, will lead to more cumulative and accurate science and therefore to faster progress in what is one of the most intriguing questions in psychology.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical tools can address this and other issues that arise from the use of awareness measures that are less than perfectly reliable. Employing tools like the one we briefly described at the end of Section 2 as well as more advanced ones (e.g., Goldstein et al, 2021) would allow the field to advance with greater confidence in the veracity of results. This, we hope, will lead to more cumulative and accurate science and therefore to faster progress in what is one of the most intriguing questions in psychology.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, further studies showed that this method overestimates unconscious effects due to the underestimation of the regression slope (Dosher, 1998;Sand & Nilsson, 2016). In response to this problem, Goldstein et al (2022) recently developed a Bayesian generative model solution for estimating the intercept of the regression model while accounting for the measurement error.…”
Section: Introductionmentioning
confidence: 99%
“…To address these questions, in the present study we aim to explore unconscious visual processing through an integrative paradigm that includes objective and subjective measures of awareness collected both during the main task (online) and in separate blocks (offline). In addition, we will examine unconscious processing through the different classical analysis strategies associated with various combinations of awareness measures and research paradigms (e.g., dissociation paradigm, trial-wise post-hoc selection), together with some new approaches recently proposed by different authors and based on models derived from Bayesian analysis and General recognition theory (Goldstein et al, 2022;Pournaghdali et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It is conceptually similar to selecting on the basis of a continuous variable, such as all d' values less than zero, and thereby ending up with a biased estimate of the mean d' of that sub-sample (for example, an estimate of less than zero for a true mean of above zero). But the suggested solutions for the latter problem (Goldstein et al, 2022;Kelley, 1947;Leganes-Fonteneau et al, 2021;4 Shanks, 2017;Yaron et al, 2023) either do not directly apply to the current one, or have not been shown to apply.…”
mentioning
confidence: 99%